STABILITY AND SUNSCREEN ACTIVITY OF NUTMEG SEED OIL EMULGEL WITH CARBOPOL 940 VARIATION AS GEL BASE - Ilma Nur Khafifa; Ayu Shabrina; M Fatchur Rochman (Universitas Muhammadiyah Magelang, 2022)
Nutmeg seed oil is one of essential oil which unstable in storage. The stability of nutmeg seed oil can be improved by being formulated into an emulgel with carbopol 940. This study was to determine the physical stability and SPF value of nutmeg oil emulgel in vitro with carbopol 940 as a gel base. Nutmeg seed oil emulgel was made with 10% nutmeg seed oil concentration and variation of carbopol 940 base, namely 0.60% (FI), 0.80% (FII), and 1.0% (FIII). Nutmeg seed oil emulgel was tested for physical stability including organoleptic, homogeneity, adhesion, dispersibility, viscosity, pH, and SPF value in vitro. Evaluation of physical stability and SPF value of nutmeg oil emulgel was carried out for 30 days of storage at 30±2°C with RH 65±5%. Quantitative data from evaluation of physical stability and SPF value were analyzed by t-test dependent. All the physical parameters showed no significant changes (p > 0.05). Emulgel were white, thick, with nutmeg seed oil odor. pH were in safe range for skin (6.12-6.90). Nutmeg seed oil emulgel had pseudo plastic rheology in day 0 and it changed into pseudoplastic-tixothropic on day 30.  The SPF value of nutmeg seed oil emulgel FI, FII, and FIII were above 8 and it did not showed significant change after 30 days of storage (p > 0.05). The SPF value of nutmeg seed oil emulgel were categorized as maximum protection.